2017
DOI: 10.1002/hbm.23713
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the order and pattern of brain structural MRI changes using change‐point analysis in premanifest Huntington's disease

Abstract: Huntington’s disease (HD) is an autosomal dominant neurodegenerative disorder that progressively affects motor, cognitive, and emotional functions. Structural MRI studies have demonstrated brain atrophy beginning many years prior to clinical onset (“premanifest” period), but the order and pattern of brain structural changes have not been fully characterized. In this study, we investigated brain regional volumes and diffusion tensor imaging (DTI) measurements in premanifest HD, and we aim to determine, (1) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 105 publications
1
25
0
Order By: Relevance
“…It is likely that the white matter changes in the earlyHD group begin many years prior to diagnosis but are not necessarily detectable in comparisons with non‐CAG expanded individuals. There is robust evidence to suggest that macrostructural white matter changes in the cortex occur prior to those in the gray matter with similar white matter microstructural changes (Paulsen et al, 2010; Tabrizi et al, 2012; Wu et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the white matter changes in the earlyHD group begin many years prior to diagnosis but are not necessarily detectable in comparisons with non‐CAG expanded individuals. There is robust evidence to suggest that macrostructural white matter changes in the cortex occur prior to those in the gray matter with similar white matter microstructural changes (Paulsen et al, 2010; Tabrizi et al, 2012; Wu et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, we only assessed associations between caudate and putamen brain structures and dual tasking performance, as these are the principle brain structures affected by the disease and sensitive to early disease changes. It is important to note that other brain structures are also affected, including the cerebellum and brain stem, 40,41 which may also influence dual tasking in HD. 42,43 Additional studies should investigate the role of other subcortical and cortical structures and dual tasking.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Gray matter and motor and cognitive functioning show significant prodromal decline in HD ( 11 , 15 , 25 , 38 41 ). Our results first confirmed that variation in these domains relates significantly to CAP, a metric reflecting disease burden and based on CAG mutation and exposure time (age) ( 13 , 42 ).…”
Section: Discussionmentioning
confidence: 99%